2020
DOI: 10.1177/1756286420966159
|View full text |Cite
|
Sign up to set email alerts
|

Rupture risk assessment for multiple intracranial aneurysms: why there is no need for dozens of clinical, morphological and hemodynamic parameters

Abstract: Introduction: A multitude of approaches have been postulated for assessing the risk of intracranial aneurysm rupture. However, the amount of potential predictive factors is not applicable in clinical practice and they are rejected in favor of the more practical PHASES score. For the subgroup of multiple intracranial aneurysms (MIAs), the PHASES score might severely underestimate the rupture risk, as only the aneurysm with the largest diameter is considered for risk evaluation. Methods: In this study, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 48 publications
0
15
1
Order By: Relevance
“…Due to the virtual deployment of a flow-diverting device, this hemodynamically unstable environment could be restabilized leading to a strong reduction of OSI. Although RRT was correlated with aneurysm rupture at well (31), its benefit with respect to treatment outcome evaluation remains limited and this trend was not reflected in our study.…”
Section: Discussioncontrasting
confidence: 58%
“…Due to the virtual deployment of a flow-diverting device, this hemodynamically unstable environment could be restabilized leading to a strong reduction of OSI. Although RRT was correlated with aneurysm rupture at well (31), its benefit with respect to treatment outcome evaluation remains limited and this trend was not reflected in our study.…”
Section: Discussioncontrasting
confidence: 58%
“…It seems that univariate models based on crude features of IA morphology may have limited prediction performance. Neyazi et al (2020) recently concluded that a high number of established morphological and hemodynamical parameters seem to have little or no effect on the prediction of aneurysm rupture. In their study, they analyzed 21 morphological and 28 hemodynamic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…However, Orning et al [ 4 ] reported that it is unreliable to use morphological features of IA in determining rupture sites in nondefinitive SAH patterns. Another study also showed that morphological and hemodynamic parameters seem to have no or only low effect on the prediction of RIA in patients with MIAs [ 16 ]. The present results showed that 39 (29.1%) RIAs had regular shapes, and 36 (23.1%) unruptured IAs had irregular shapes.…”
Section: Discussionmentioning
confidence: 99%